The effect of prolonged dietary nitrate supplementation on atherosclerosis development. (February 2016) - Marsch, Elke; Theelen, Thomas L.; Janssen, Ben J.A.; Briede, Jacco J.; Haenen, Guido R.; Senden, Joan M.G.; van Loon, Lucas J.C.; Poeze, Martijn; Bierau, Jörgen; Gijbels, Marion J.; Daemen, Mat J.A.P.; Sluimer, Judith C.
Abstract: Background: Short term dietary nitrate or nitrite supplementation has nitric oxide (NO)-mediated beneficial effects on blood pressure and inflammation and reduces mitochondrial oxygen consumption, possibly preventing hypoxia. As these processes are implicated in atherogenesis, dietary nitrate was hypothesized to prevent plaque initiation, hypoxia and inflammation. Aims: Study prolonged nitrate supplementation on atherogenesis, hypoxia and inflammation in low density lipoprotein receptor knockout mice (LDLr −/− ). Methods: LDLr −/− mice were administered sodium-nitrate or equimolar sodium-chloride in drinking water alongside a western-type diet for 14 weeks to induce atherosclerosis. Plasma nitrate, nitrite and hemoglobin-bound nitric oxide were measured by chemiluminescence and electron parametric resonance, respectively. Results: Plasma nitrate levels were elevated after 14 weeks of nitrate supplementation (NaCl: 40.29 ± 2.985, NaNO3 : 78.19 ± 6.837, p < 0.0001). However, prolonged dietary nitrate did not affect systemic inflammation, hematopoiesis, erythropoiesis and plasma cholesterol levels, suggesting no severe side effects. Surprisingly, neither blood pressure, nor atherogenesis were altered. Mechanistically, plasma nitrate and nitrite were elevated after two weeks (NaCl: 1.0 ± 0.2114, NaNO3 : 3.977 ± 0.7371, p < 0.0001), but decreased over time (6, 10 and 14 weeks). Plasma nitrite levels even reached baseline levels at 14 weeks (NaCl: 0.7188 ± 0.1072, NaNO3 : 0.9723 ± 0.1279 p = 0.12). Also hemoglobin-bound NO levels were unaltered after 14 weeks. This compensation was not due to altered eNOS activity or conversion into peroxynitrite and other RNI, suggesting reduced nitrite formation or enhanced nitrate/nitrite clearance. Conclusion: Prolonged dietary nitrate supplementation resulted in compensation of nitrite and NO levels and did not affect atherogenesis or exert systemic side effects. Highlights: Long term dietary nitrate supplementation does not affect atherosclerosis. No systemic side effects are observed upon long term dietary nitrate. Plasma nitrate, nitrite and NO are compensated for upon long term dietary nitrate.